Drug Screening Implicates Chondroitin Sulfate as a Potential Longevity Pill - Ewald, Collin Y. (Frontiers in Aging, 2021)
Discovering compounds that promote health during aging (“geroprotectors”) is key to the retardation of age-related pathologies and the prevention of chronic age-related diseases. In in-silico and model organisms’ lifespan screens, chondroitin sulfate has emerged as a geroprotective compound. Chondroitin sulfate is a glycosaminoglycan attached to extracellular matrix proteins and is naturally produced by our body. Oral supplementation of chondroitin sulfate shows a high tolerance in humans, preferable pharmacokinetics, a positive correlation with healthy human longevity, and efficacy in deceleration of age-related diseases in randomized clinical trials. We have recently shown that chondroitin sulfate supplementation increases the lifespan of C. elegans. Thus, chondroitin sulfate holds the potential to become a geroprotective strategy to promote health during human aging. This review discusses the two major potential mechanisms of action, extracellular matrix homeostasis and inhibition of inflammation, that counteract age-related pathologies upon chondroitin sulfate supplementation.